Petrology, geochemistry, and Sr, Nd isotopes of mantle xenolith in Nghia Dan alkaline basalt (West Nghe An): implications for lithospheric mantle characteristics beneath the region - Huong, Tran Thi; Hoang, Nguyen (Vietnam Journal of Earth Sciences, 2018)
Study of petrological and geochemical characteristics of mantle peridotite xenoliths in Pliocene alkaline basalt in Nghia Dan (West Nghe An) was carried out. Rock-forming clinopyroxenes, the major trace element containers, were separated from the xenoliths to analyze for major, trace element and Sr-Nd isotopic compositions. The data were interpreted for source geochemical characteristics and geodynamic processes of the lithospheric mantle beneath the region. The peridotite xenoliths being mostly spinel-lherzolites in composition, are residual entities having been produced following partial melting events of ultramafic rocks in the asthenosphere. They are depleted in trace element abundance and Sr-Nd isotopic composition. Some are even more depleted as compared to mid-ocean ridge mantle xenoliths. Modelled calculation based on trace element abundances and their corresponding solid/liquid distribution coefficients showed that the Nghia Dan mantle xenoliths may be produced of melting degrees from 8 to 12%. Applying various methods for two-pyroxene temperature- pressure estimates, the Nghia Dan mantle xenoliths show ranges of crystallization temperature and pressure, respectively, of 1010-1044°C and 13-14.2 kbar, roughly about 43km. A geotherm constructed for the mantle xenoliths showed a higher geothermal gradient as compared to that of in the western Highlands (Vietnam) and a conductive model, implying a thermal perturbation under the region. The calculated Sm-Nd model ages for the clinopyroxenes yielded 127 and 122 Ma. If the age is meaningful it suggests that there was a major geodynamic process occurred beneath Western Nghe An in the middle- Early Cretaceous that was large enough to cause perturbation in the evolutional trend of the Sm-Nd isotopic system. References An A-R., Choi S.H., Yu Y-g., Lee D-C., 2017. Petrogenesis of Late Cenozoic basaltic rocks from southern Vietnam. Lithos, 272-273 (2017), 192-204. Anders E., Grevesse N., 1989. Abundances of the elements: meteorite and solar. Geochimica et Cosmochimica Acta, 53, 197-214. Anderson D.L, 1994. The subcontinental mantle as the source of continental flood basalts; the case against the continental lithosphere mantle and plume hear reservoirs. Earth and Planetary Science Letter, 123, 269-280. Arai S., 1994. Characterization of spinel peridotites by olivine-spinel compositional relationships: review and interpretation. Chemical Geology, 113, 191-204. Ballhaus C., Berry R.G., Green D.H., 1991. High pressure experimental calibration of the olivine orthopyroxene-spinel oxygen geobarometer: implications for the oxidation state of the upper mantle. Contributions to Mineralogy and Petrology, 107, 27-40. Barr S.M. and MacDonald A.S., 1981. Geochemistry and geochronology of late Cenozoic basalts of southeast Asia: summary. Geological Society of America Bulletin, 92, 508-512. Brey G.P., Köhler T., 1990. Geothermobarometry in four-phase lherzolite II. New thermobarometers, and practical assessment of existing thermobarometers. Journal of Petrology, 31, 1353-1378. Briais A., Patriat P., Tapponnier P., 1993. Updated interpretation of magnetic anomalies and seafloor spreading stages in the South China Sea, implications for the Tertiary tectonics of SE Asia. Journal of Geophysical Research, 98, 6299-6328. Carlson R.W., Irving A.J., 1994. Depletion and enrichment history of subcontinental lithospheric mantle: an Os, Sr, Nd and Pb isotopic study of ultramafic xenoliths from the northwestern Wyoming Craton. Earth and Planetary Science Letters, 126, 457-472. Carlson R.W., Lugmair G.W., 1979. Sm-Nd constraints on early lunar differentiation and the evolution of KREEP. Earth and Planetary Science Letters, 45, 123-132. Carlson R.W., Lugmair G.W., 1981. Sm-Nd age of lherzolite 67667: implications for the processes involved in lunar crustal formation. Earth and Planetary Science Letters, 56, 1-8. Choi H.S., Mukasa S.B., Zhou X-H., Xian X-G.H., Andronikov A.V., 2008. Mantle dynamics beneath East Asia constrained by Sr, Nd, Pb and Hf isotopic systematics of ultramafic xenoliths and their host basalts from Hannuoba, North China. Chemical Geology, 248, 40-61. Choi S.H., Jwa Y.-J., Lee H.Y., 2001. Geothermal gradient of the upper mantle beneath Jeju Island, Korea: evidence from mantle xenoliths. Island Arc, 10, 175-193. Choi S.H., Kwon S-T., Mukasa S.B., Sagon H., 2005. Sr-Nd-Pb isotope and trace element systematics of mantle xenoliths from Late Cenozoic alkaline lavas, South Korea. Chemical Geology, 22, 40-64. Cox K.G., Bell J.D., Pankhurst R.J., 1979. The Interpretation of Igneous Rocks. George Allen & Unwin. Cung Thuong Chi, Dorobek S.L., Richter C., Flower M., Kikawa E., Nguyen Y.T., McCabe R., 1998. Paleomagnetism of Late Neogene basalts in Vietnam and Thailand: Implications for the Post-Miocene tectonic history of Indochina. In: Flower M.F.J., Chung, S.L., Lo, C.H., (Eds.). Mantle Dynamics and Plate Interactions in East Asia. Geodynamics Ser, American Geophysical Union, 27, 289-299. De Hoog J.C.M., Gall L., Cornell D.H., 2010. Trace-element geochemistry of mantle olivine and application to mantle petrogenesis and geothermobarometry. Chemical Geology, 270, 196-215. DePaolo D. J., 1981. Neodymium isotopes in the Colorado Front Range and crust - mantle evolution in the Proterozoic. Nature, 291, 193-197. DePaolo D.J., Wasserburg G.J., 1976. Nd isotopic variations and petrogenetic models. Geophysical Research Letters, 3(5), 249-252. Doi: https://doi.org/10.2113/gselements.13.1.11. Embey-Isztin A., Dobosi G., Meyer H.-P., 2001. Thermal evolution of the lithosphere beneath the western Pannonian Basin: evidence from deep-seat xenoliths. Tectonophysics, 331, 285-306. Fedorov P.I., Koloskov A.V., 2005. Cenozoic volcanism of Southeast Asia. Petrologiya, 13(4), 289-420. Frey F.A., Prinz M., 1978. Ultramafic inclusions from San Carlos, Arizona: Petrologic and geochemical data bearing on their Petrogenesis. Earth and Planetary Science Letters, 38, 129-176. Garnier V., Ohmenstetter D., Giuliani G., Fallick A.E., Phan T.T., Hoang Q.V., Pham V.L., Schawarz D., 2005. Basalt petrology, zircon ages and sapphire genesis from Dak Nong, southern Vietnam. Mineralogical Magazine, 69(1), 21-38. Gast P.W., 1968. Trace element fractionation and the origin of tholeiitic and alkaline magma types. Geochimica et Cosmochimica Acta, 32, 1057-1086. Gorshkov A.P, Ivanenko A.N., Rashidov V.A., 1984. Hydro-magnetic investigations of submarine volcanic zones in the marginal seas of Pacific Ocean (Novovineisky and Bien Dong seas). Pacific Ocean Geology, 1, 13-20. Gorshkov A.P., 1981. Investigation of submarine volcanoes during the 10th course of scientific research vessel ‘Volcanolog’. Volcanology and Seismology, 6, 39-45 (in Russian). Hart S.R., 1988. Heterogeneous mantle domains: signatures, genesis and mixing chronologies. Earth and Planetary Science Letters, 90, 273-296. Hirose K., Kushiro I., 1993. Partial melting of dry peridotites at high pressures: determination of composition of melts segregated from peridotite using aggregate of diamond. Earth Planet Science Letters, 114, 477-489. Hoang-Thi H.A., Choi S.H., Yongjae Yu Y-g., Pham T.H., Nguyen K.H., Ryu J-S., 2018. Geochemical constraints on the spatial distribution of recycled oceanic crust in the mantle source of late Cenozoic basalts, Vietnam. Lithos, 296-299 (2018), 382-395. Izokh A.E., Smirnov S.Z., Egorova V.V., Tran T.A., Kovyazin S.V., Ngo T.P., Kalinina V.V., 2010. The conditions of formation of sapphire and zircon in the areas of alkali-basaltoid volcanism in Central Vietnam. Russian Geology and Geophysics, 51(7), 719-733. Johnson K.T., Dick H.J.B. and Shimizu N., 1990. Melting in the oceanic upper mantle: An ion microprobe study of diopsides in abyssal peridotites. Journal of Geophysical Research (solid earth), 95, 2661-2678. Kölher T.P., Brey G.P., 1990. Calcium exchange between olivine and clinopyroxene calibrated as a geothermobarometer for natural peridotites from 2 to 60 kb with applications. Geochimica et Cosmochimica Acta, 54(9), 2375-2388. Kushiro I., 1996. Partial melting of a fertile mantle peridotite at high pressure: An experimental study using aggregates of diamond. In: A. Basu and S.R. Hart (Eds.), Earth Processes: Reading the Isotopic Code. AGU Monograph, 95, 109-122. Kushiro I., 1998. Compositions of partial melts formed in mantle peridotites at high pressures and their relation to those of primitive MORB. Physics of Earth and Planetary Interiors, 107, 103-110. Latin D., White N., 1990. Generating melt during lithospheric extension: Pure shear vs. simple shear. Geology, 18, 327-331. Lee T.-y. and Lawver L., 1995. Cenozoic plate reconstruction of Southeast Asia. In: M.F.J. Flower, R.J. McCabe and T.W.C. Hilde (Editors), Southeast Asia Structure, Tectonics, and Magmatism. Tectonophysics, 85-138. Li C-F., et al., 2015. Seismic stratigraphy of the central South China Sea basin and implications for neotectonics. Journal of Geophysical Research (solid earth), 120, 1377-1399. Doi:10.1002/2014JB011686. Li C.-F., et al., 2014. Ages and magnetic structures of the South China Sea constrained by deep tow magnetic surveys and IODP Expedition 349 Geochemistry, Geophysics, Geosystems, 14, 4958-4983. Malinovsky A.I., Rashidov V.A., 2015. Compositional characteristics of sedimentary and volcano-sedimentary rocks of Phu Quy-Catwick island group in the continental shelf of Vietnam. Bulletin of Kamchatka Regional Association of ‘Educational - Scientific’ Center, Earth Sciences, 27(3), 12-34 (in Russian with English summary). McCulloch M.T., Wasserburg G.J., 1978. Sm-Nd and Rb-Sr chronology of continental crust formation. Science, 200(4345), 1003-1011. Menzies M.A., Arculus R.L., Best M.G., et al., 1987. A record of subduction process and within-plate volcanism in lithospheric xenoliths of the southwestern USA. In P.H. Nixon (Editor), Mantle Xenoliths, John Wiley & Sons, Chichester, 59-74. Nguyen Hoang, Ogasawara M., Tran Thi Huong, Phan Van Hung, Nguyen Thi Thu, Cu Sy Thang, Pham Thanh Dang, Pham Tich Xuan, 2014. Geochemistry of Neogene Basalts in the Nghia Dan district, western Nghe An. J. Sci. of the Earth, 36, 403 -412. Nguyen Kinh Quoc, Nguyen Thu Giao, 1980. Cenozoic volcanic activity in Viet Nam. Geology and Mineral Resources, 2, 137-151 (in Vietnamese with English abstract). Nixon P.H., 1987 (Editor). Mantle xenoliths. John Wiley and Sons, 844p. Norman M.D. and Garcia M.O., 1999. Primitive magmas and source characteristics of the Hawaiian plume: petrology and geochemistry of shield picrites. Earth and Planetary Science Letters, 168, 27-44. Pollack H.N., Chapman D.S., 1977. On the regional variation of heat flow, geotherms and lithospheric thickness. Tectonophysics, 38, 279-296. Putirka K., 2008. Thermometers and Barometers for Volcanic Systems. In: Putirka, K., Tepley, F. (Eds.), Minerals, Inclusions and Volcanic Processes, Reviews in Mineralogy and Geochemistry, Mineralogical Soc. Am., 69, 61-120. Putirka K.D., 2017. Down the craters: where magmas stored and why they erupt. Methods and Further Reading. Supplement to February 2017 issue of Elements, 3(1), 11-16. Putirka K.D., Johnson M., Kinzler R., Longhi J., Walker D., 1996. Thermobarometry of mafic igneous rocks based on clinopyroxene-liquid equilibria, 0-30 kbar. Contributions to Mineralogy and Petrology, 123, 92-108. Putirka K.D., Mikaelian H., Ryerson F., Shaw H., 2003. New clinopyroxene-liquid thermobarometers for mafic, evolved, and volatile-bearing lava compositions, with applications to lavas from Tibet and the Snake River Plain, Idaho. American Mineralogist, 88, 1542-1554. Qi Q., Taylor L.A., Zhou X., 1995. Petrology and geochemistry of mantle peridotite xenoliths from SE China. Journal of Petrology, 36, 55-79. Sachtleben T.H., Seck H.A., 1981. Chemical control on the Al-solubility in orthopyroxene and its implications on pyroxene geothermometry. Contributions to Mineralogy and Petrology, 78, 157-65. Shaw D.M., 1970. Trace element fractionation during anataxis. Geochimica et Cosmochimica Acta, 34, 237-243. Sun S-S, McDonough W.F., 1989. Chemical and isotopic systematics of oceanic basalts: implications for mantle composition and processes. In Saunders A.D. and Norry, M.J. (eds) Magmatism in the Ocean Basins. Geological Society Special Publication, 42, 313-345. Takahashi E., 1986. Melting of a dry peridotite KLB-1 up to 14 Gpa: implications on the origin of peridotite upper mantle. J. Geophysical Research, 91, 9367-9382. Takahashi E., Kushiro I., 1983. Melting of a dry peridotite at high pressure and basalt magma genesis. American Mineralogist, 68, 859-879. Tamaki K., 1995. Upper mantle extrusion tectonics of southeast Asia and formation of western Pacific backarc basins. In: International Workshop: Cenozoic Evolution of the Indochina Peninsula, Hanoi/Do Son, April, p.89 (Abstract with Programs). Tapponnier P., Lacassin R., Leloup P.H., Shärer U., Dalai Z., Haiwei W., Xiaohan L., Shaocheng J., Lianshang Z., Jiayou Z., 1990. The Ailao Shan/Red River metamorphic belt: Tertiary left-lateral shear between Indochina and South China. Nature, 343(6257), 431-437. Tapponnier P., Peltzer G., La Dain A.Y., Armijo R., Cobbold P., 1982. Propagating extrusion tectonics in Asia: New insights from simple experiments with plasticine. Geology, 7, 611-616. Tatsumoto M., Basu A.R., Huang W., Wang J., Xie G., 1992. Sr, Nd, and Pb isotopes of ultramafic xenoliths in volcanic rocks of eastern China: enriched components EMI and EMII in subcontinental lithosphere. Earth Planet Sci. Letters, 113, 107-128. Taylor S.R., McLennan S.M., 1981. The composition and evolution of the continental crust: rare earth element evidence from sedimentary rocks. Philosophical Transactions of the Royal Society of London, 301, 381-399. Tu K., Flower M.F.J., Carlson R.W., Xie G-H., 1991. Sr, Nd, and Pb isotopic compositions of Hainan basalt (south China): Implications for a subcontinental lithosphere Dupal source. Geology, 19, 567-569. Tu K., Flower M.F.J., Carlson R.W., Xie G-H., Zhang M., 1992. Magmatism in the South China Basin 1. Isotopic and trace-element evidence for an endogenous Dupal component. Chemical Geology, 97, 47-63. Warren J.M., 2016. Global variations in abyssal peridotite compositions. Lithos, 248-251, 193-219. Webb S.A., Wood B.J., 1986. Spinel pyroxene- garnet relationships and their dependence on Cr/Al ratio. Contributions to Mineralogy and Petrology, 92, 471-480. Wells P.R.A., 1977. Pyroxene thermometry in simple and complex systems. Contributions to Mineralogy and Petrology, 62, 129-139. Whitford-Stark J.L., 1987. A survey of Cenozoic olcanism on mainland Asia, special paper, 213. Geological Society of America, 74p. Workman R.K., Hart S.R., 2005. Major and trace element composition of the depleted MORB mantle (DMM). Earth and Planetary Science Letters, 231, 53-72. Zhou P., Mukasa S., 1997. Nd-Sr-Pb isotopic, and major- and trace-element geochemistry of Cenozoic lavas from the Khorat Plateau, Thailand, sources and petrogenesis. Chemical Geology, 137, 175-193. Zindler A., Hart S.R., 1986. Chemical geodynamics. Annual Review of Earth and Planetary Sciences, 14, 493-571.